A novel crop water analysis system: identification of water stress tolerant genotypes of canola (Brassica napus L.) using non‐invasive magnetic turgor pressure probes. Issue 5 (28th April 2014) - Kant, Surya; Burch, David; Ehrenberger, Wilhelm; Bitter, Rebecca; Rüger, Simon; Mason, John; Zimmermann, Ulrich; Spangenberg, German; Léon, J.
Abstract Changing global climatic conditions and irrigation water shortages impose water stress conditions on crops. To develop genotypes tolerant to water stress necessitates reliable high‐throughput methods to study plant water status and water stress tolerance mechanisms. We report the use of a non‐destructive, automated, precise and rapid system for assessing real‐time water status in canola plants. Leaf patch clamp pressure probes were clamped on the leaves of four different genotypes of canola grown under field conditions. The data generated diurnal curves characterizing the pattern of turgor pressure maintenance within the leaves. A novel methodology termed 'inverse hysteresis' was developed to measure relative water stress levels in plants using the probe‐derived data. The inverse hysteresis data show that genotypes CT12 and CT15 had a higher ability to withstand water stress and were more tolerant to water stress than DS23 and DS35. The chlorophyll content and seed yield were also higher in CT12 and CT15. This novel analytical tool for monitoring water status in canola plants will be of great benefit in other crop species to efficiently screen genotypes for water stress tolerance.